2018
DOI: 10.1186/s13071-017-2601-y
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and biotype of invasive Anopheles stephensi in Mannar Island of Sri Lanka

Abstract: BackgroundAnopheles stephensi, the major vector of urban malaria in India, was recently detected for the first time in Sri Lanka in Mannar Island on the northwestern coast. Since there are different biotypes of An. stephensi with different vector capacities in India, a study was undertaken to further characterise the genotype and biotype of An. stephensi in Mannar Island.MethodsMosquito larvae were collected in Pesalai village in Mannar and maintained in the insectary until adulthood. Adult An. stephensi were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 28 publications
2
42
0
Order By: Relevance
“…Aedes aegypti is the main vector of Dengue and Dengue hemorrhagic fevers 12,13 . Anopheles stephensi larvae is a major malaria vector 14 . Hence researchers continuously study to control these larvae with herbal extracts and found Tridax procumbens L. 15 and Leucas aspera L. 16 with positive results.…”
Section: Resultsmentioning
confidence: 99%
“…Aedes aegypti is the main vector of Dengue and Dengue hemorrhagic fevers 12,13 . Anopheles stephensi larvae is a major malaria vector 14 . Hence researchers continuously study to control these larvae with herbal extracts and found Tridax procumbens L. 15 and Leucas aspera L. 16 with positive results.…”
Section: Resultsmentioning
confidence: 99%
“…stephensi in the Horn of Africa poses considerable health risks of increased receptivity and local transmission of malaria in the increasing urban African settings requiring realignment of malaria control programs. Its frequent presence in human-made aquatic habitats [37] indicates that a simple bifurcation between urban and rural settings may be misleading and is context dependent. Additionally, urban populations are also at increased risk of Aedes -borne diseases, which are increasing in incidence in Africa [38–41].…”
Section: Discussionmentioning
confidence: 99%
“…Kerala state and Lakshadweep islands [33]. Similarly, this species invaded Sri Lanka (from India via water carrying eggs in boats) through the narrow Palk Strait (southward) [33,34].…”
Section: Discussionmentioning
confidence: 99%